Stellar population properties of individual massive early-type galaxies at 1.4 < z < 2. Issue 1 (10th December 2019) - Lonoce, I; Maraston, C; Thomas, D; Longhetti, M; Parikh, T; Guarnieri, P; Comparat, J
ABSTRACT: We analyse publicly available, individual spectra of four massive (M10^11 M_ ) early-type galaxies with redshifts in the range 1.4 ≤ z ≤ 2 to determine their stellar content, extending our previous work up to z ∼ 2. The wide wavelength range of the VLT/X-Shooter spectroscopic data in the UV–Optical–NIR arms along with the availability of spectro-photometry allows us to explore different techniques to obtain the stellar population properties, namely through age/metallicity-sensitive spectral indices, full spectral fitting, and broad-band photometric fitting. Moreover, together with the widely used optical Lick indices, we consider further indices in the UV rest frame, and demonstrate that UV indices significantly help the accuracy of the resulting population parameters. We find galaxy ages ranging from 0.2 to 4 Gyr, where the oldest galaxy is found at the lowest redshift, with an excellent agreement between ages determined via indices, full spectral fitting, or broad-band colours. These ages are in perfect agreement with ages of local galaxies at the same velocity dispersion when we assume pure passive evolution. Total metallicities derived from indices show some scatter (between less than half-solar to very high values, [ Z / H ] ∼ 0.6). We speculate on possible mechanisms explaining these values, but given the sample size and low S/N of the spectra no conclusion can be made. Indices in the UV rest frame generally lead to similar conclusions as optical indices. For the oldest galaxy (4 Gyr), we show that its UV indices can only be explained by stellar population models including a UV contribution from old stellar populations, suggesting that old, UV bright populations start to inhabit mature galaxies of a few Gyr of age. This is the highest redshift ( z ∼ 1.4) detection of the UV upturn up to date.